2021
DOI: 10.1001/jamaophthalmol.2021.4323
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Bias and the Association of Redaction of Identifiers With Residency Application Screening Scores

Abstract: IMPORTANCE Diversity in the ophthalmology profession is important when providing care for an increasingly diverse patient population. However, implicit bias may inadvertently disadvantage underrepresented applicants during resident recruitment and selection.OBJECTIVE To evaluate the association of the redaction of applicant identifiers with the review scores on ophthalmology residency applications as an intervention to address implicit bias. DESIGN, SETTING, AND PARTICIPANTSIn this quality improvement study, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The most significant increases were among Black physicians selected to be interviewed. Similarly, Pershing et al (2021) found that with a holistic approach, the redaction of racial identifiers (e.g., names) was not associated with a difference in application scores for interviews between Black physicians and White physicians.…”
Section: Strategies To Mitigate Anti-black Racism In Selectionmentioning
confidence: 91%
See 1 more Smart Citation
“…The most significant increases were among Black physicians selected to be interviewed. Similarly, Pershing et al (2021) found that with a holistic approach, the redaction of racial identifiers (e.g., names) was not associated with a difference in application scores for interviews between Black physicians and White physicians.…”
Section: Strategies To Mitigate Anti-black Racism In Selectionmentioning
confidence: 91%
“…Additionally, all interviewers should use rating forms, a set of clearly defined job performance-related questions (to avoid illegal questions), and standardized performance-based criteria with a scoring rubric (Consul et al, 2021;Gardner et al, 2018). We also suggest blinding reviewers to academic metrics and photographs prior to the interview to ensure the risk of bias is reduced (Capers, 2020;Pershing et al, 2021). Capers et al, (2018) saw a significant increase in the number of Black physicians selected after implementing the strategies outlined above.…”
Section: Strategies To Mitigate Anti-black Racism In Selectionmentioning
confidence: 99%
“…However, anonymising job applications can have unpredictable effects, with some studies finding that the practice resulted in increasing women’s chances of interview, and others finding a reduced chance [ 21 , 22 ]. An investigation of the effects of anonymisation on recruitment to an ophthalmology residency programme found no significant effect on applicant scores overall or specifically for female candidates [ 16 ]. When applications are anonymised, reviewers can seek implicit signals to categorise applicants according to gender, and in doing so, use stereotypes of employment patterns and communications styles, thus activating biases which the anonymisation procedure sought to suppress [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gender-blinding is an attractive strategy because it removes the source of bias, and does not disadvantage other groups of candidates [ 14 ]. This strategy has been shown to be successful in fields such as astronomy and music [ 14 , 15 ], but other studies in ophthalmology and molecular biology have found no effect [ 16 , 17 ] and overall, evidence is limited [ 18 ]. We sought to investigate its effectiveness in recruitment to an early career training programme for junior doctors, the Academic Internship Track (AIT).…”
Section: Introductionmentioning
confidence: 99%
“…Diversifying residency training programs must come with departmental prioritization and commitment to diversity, equity, and inclusion. In this issue of JAMA Ophthalmology , Pershing et al present data on implicit bias and the association of redaction with review scores on residency application screening. Faculty reviewed randomized sets of redacted and unredacted applications and found no significant differences in review scores of redacted vs unredacted applications based on applicants’ sex, underrepresented in medicine (URiM) status, or international medical graduate status.…”
mentioning
confidence: 99%